Quantitative Proteomics Reveals the Effects of Resveratrol on High‐Altitude Polycythemia Treatment. Issue 14 (6th July 2020) - Deng, Bingnan; Liu, Weili; Pu, Lingling; Wang, Xinxing; Duan, Ruifeng; Wang, Tianhui; Wang, Zirou; Du, Lianqun; Gao, Zhixian; Chen, Zhaoli
Abstract: High‐altitude polycythemia (HAPC) is a common plateau chronic disease in which red blood cells are compensatory hyperproliferative due to high altitude hypoxic environment. HAPC severely affects the physical and mental health of populations on the plateau. However, the pathogenesis and treatment of HAPC has been rarely investigated. Here, the hypoxia‐induced HAPC model of rat is established, in which hemoglobin concentration significantly increases and platelets clearly decrease. The effect of resveratrol upon hypoxia enables HAPC remission and makes hemoglobin and platelet tend to a normal level. Furthermore, quantitative proteomics is applied to investigate the plasma proteome variation and the underlying molecular regulation during HAPC occurrence and treatment with resveratrol. Hypoxia promotes erythrocyte developing and differentiating and disrupts cytoskeleton organization. Notably, the resveratrol administration reverses the proteome change pattern due to hypoxia and contributes to plateau adaption. Quantitative verification of differentially expressed proteins confirms the roles of resveratrol in HAPC. Resveratrol is expected to be useful for HAPC treatment.